Harmonic Elimination using Active Power Filter for Non-Sinusoidal Voltage Source System - ปานแป้น ชาคริต; อารีรักษ์ กองพล; อารีรักษ์ กองพัน (Srinakharinwirot University Engineering Journal, 2019)
This paper presents harmonic elimination using active power filter for non-sinusoidal voltage source system. The instantaneous power theory (PQ) with positive sequence voltage detector (PSVD) is used for harmonic detection to calculate the reference current. The PI–controller is applied for compensating current control and DC bus voltage control. This controller is used with PWM switching technique. Moreover, the Matlab Simulink is applied for simulation in the paper. The simulation results show that the active power filter with PI–controller can provide the good performance to eliminate the harmonic for all loads in non-sinusoidal voltage source system. In the paper, the performance index is of source current after compensation. In addition, the after compensation can follow the IEEE Std.519 – 2014 and IEEE std.1459 – 2010.